1997
DOI: 10.1183/09031936.97.10020280
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment in fibrosing alveolitis: relationship to reversible disease on thin section computed tomography

Abstract: Thin-section computed tomography (CT) provides a reproducible method of quantifying global disease extent and can also discriminate between fibrotic disease, with predominance of reticular abnormalities, and reversible inflammatory cell infiltration, shown as ground-glass attenuation.The aim of this study was to determine whether functional impairment varied according to the presence of ground-glass attenuation on CT, independently of extent of disease on CT, demographic factors, smoking history, therapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 31 publications
1
33
0
2
Order By: Relevance
“…To evaluate disease progression, adding such subscore might be of additional value. In other studies by Wells et al [18,19] it was shown that CT appearances were of prognostic value in fibrosing alveolitis and that they are likely to play an increasing role in disease staging in these conditions. The therapeutic dilemma for clinicians who manage patients with sarcoidosis is when to prescribe steroids and/or immunosuppressive agents, which are widely used to treat fibrosis and may have a role in slowing the progression of the inflammation involved in the pathophysiological process of sarcoidosis towards fibrotic disease; thus, accurate staging of the disease extent is mandatory to guide therapeutic strategies aimed to avoid potentially preventable functional impairment in sarcoidosis.…”
Section: Hrct and Respiratory Functional Impairmentmentioning
confidence: 91%
See 1 more Smart Citation
“…To evaluate disease progression, adding such subscore might be of additional value. In other studies by Wells et al [18,19] it was shown that CT appearances were of prognostic value in fibrosing alveolitis and that they are likely to play an increasing role in disease staging in these conditions. The therapeutic dilemma for clinicians who manage patients with sarcoidosis is when to prescribe steroids and/or immunosuppressive agents, which are widely used to treat fibrosis and may have a role in slowing the progression of the inflammation involved in the pathophysiological process of sarcoidosis towards fibrotic disease; thus, accurate staging of the disease extent is mandatory to guide therapeutic strategies aimed to avoid potentially preventable functional impairment in sarcoidosis.…”
Section: Hrct and Respiratory Functional Impairmentmentioning
confidence: 91%
“…The HRCT uses short scanning times and thin collimation, making it possible to demonstrate lung parenchyma in detail and detect abnormal changes of the lung parenchyma at an early stage [4,5,6,7,8,9,10,11]. Moreover, in several diffuse lung diseases HRCT abnormalities appeared to be useful in evaluating parameters of disease activity and functional impairment to predict prognosis, and in assessing response to therapy [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Such correlations take no account of the regional inhomogeneity of fibrosing lung disease and account for the discrepant results between studies that have sought relationships between histopathological severity of disease and physiological disturbance [71,72]. This is in contrast to more recent work which has shown much stronger correlations between PFT data and global assessment with CT of disease extent [68,73].…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 83%
“…These studies, with relatively small numbers of patients, demonstrated that architectural distortion, honeycombing, traction bronchiectasis and large cysts are invariably irreversible, (micro)nodular disease is in most cases reversible, but ground-glass, irregular linear opacities and interlobular septal thickening can be reversible but quite often are not and can progress to fibrosis [11][12][13][14][15][16]. Thus, evaluating the reversibility of disease by HRCT appears to be possible only in retrospect with serial data.…”
Section: Radiological Imaging Conventional Chest Radiographymentioning
confidence: 99%